10–2 Improving quality of chest compressions amongst medical and nursing staff through deliberate in-situ simulated practice with feedback: the impact of repeated training. (17th November 2017) - Korb, C; Lofton, L; Balnta, C; MacGloin, H; Goodliffe, K; Buckle, C; McGee, J; Lane, M; Burmester, M
Abstract : Background: Quality of chest compressions underpins resuscitation outcomes with poorer performance leading to lower survival rates. 1 We aimed to analyse whether deliberate practice of chest compressions with real-time feedback improves quality of compression amongst PICU nursing and medical staff and the impact of repeated training at 2, 4 and 6 months. Methods: Prospective, longitudinal study with in-situ workshops utilising Resusci Baby® QCPR®. Hand position, correct & average rate, depth and recoil were recorded and resulted in overall summative scores. Study protocol and consent procedure were approved by the Trusts Research Office. Results: 56 participants (14 doctors, 42 nurses) of which 49 (87.5%) completed all workshops. There was significant improvement on overall, depth, recoil and rate scores immediately after feedback for all workshops (Table 1). A significant improvement was also noted on baseline scores over time: complete recoil from 2nd session (72%, IQR 20–98% vs. 98%, IQR 82–100%, p=0.003); overall score, depth, correct and average rate at 4 months in comparison to the first session (84%, IQR 49–94% vs. 95%, IQR 87–98%, p<0.001; 97%, IQR 45–100% vs. 100%, IQR 98–100%, p<0.001; 14%, IQR 1–83% vs. 65%, IQR 30–90%, p=0.002; 119bpm, IQR 113–129bpm vs. 112bpm, IQR 101–118bpm, p=0.01, respectively). Hand position baseline scores did not significantly change over time. Conclusion: Deliberate practice of chest compressions with continuous real-time feedback improves quality of compressions amongst PICU nursing and medical staff. This improvement is noted immediately and continues over time with repeated training. Reference: D Yannopoulos, TP Aufderheide, BS Abella, et al . Quality of CPR: An important effect modifier in cardiac arrest clinical outcomes and intervention effectiveness trials. Resuscitation 2015;94:106–13.